Breast milk vs. non-nutritive sucking to reduce pain from minor invasive procedures in neonates - Marisya, Sevina; Tjipta, Guslihan Dasa; Supriatmo, Supriatmo; Azlin, Emil (Paediatrica Indonesiana, 2013)
Background Neonates undergo many uncomfortable, invasive minor procedures during their first hospital stay. Nonpharmacological interventions may provide valuable alternatives for pain relief in neonates during minor procedures. Objective To compare the analgesic effect of orally administered breast milk vs. non-nutritive sucking (NNS) in neonates who underwent minor invasive procedures. Methods A randomized, open trial was performed at the Haji Adam Malik Hospital from September to December 2009. Subjects were 96 healthy, term infants who received injections of either intramuscular hepatitis B immunization or vitamin K. Subjects were randomly allocated into two groups, those were the breast milk group (n = 48) and the NNS group (n= 48). Breast milk and NNS were given two minutes before the injection. The events were recorded by video recorder. Transcutaneous heart rate, oxygen saturation and crying times were recorded. Two observers used the premature infant pain profile (PIPP) scale to evaluate all subjects. Result.s In the breast milk group, there was significant reduction in meanPIPPscore (P= 0.001) and mean crying time (P= 0.03) compared to the NNS group. There were no significant differences in mean PIPP score and crying times between males and females (P= 0.4 and P=0.5, respectively). However, there was a significantly lower mean PIPP score for vitamin K injection than for hepatitis B immunization (P=0.002), although mean crying times were not significantly different (P= 0.06). We observed significantly less Oz desaturation at 150 seconds postinjection in the breast milk group compared to that of the NNS group. However, there was no significant difference in heart rate between the two groups throughout the observation period. Conclusion Breast milk administered before an invasive minor procedure effectively reduces pain in neonates. Breast milk administered to neonates prior to injection has reduced mean PIPP scores, crying times, and Oz desaturation, compared to neonates who received NNS in the form of pacifiers.